Omnipotent Humility: Reflections on the Essence of Christianity - Caamaño, José (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2021)
Through these reflections, the author places us before the challenge of considering the essence of Christianity as something that escapes the shortcut of abstraction. The truth in the Bible is fidelity to the Covenant, love and compassion to the poor, be a refuge for the one who lost his homeland. In fact, the Decalogue (as later the Beatitudes) proposes a set of relationships that come to restore the wound caused by humanity’s claim to carry things forward by building the idols that derive from self-divinization. The tension between truth as a set of disincarnated precepts and as a healed relationship with our environment inevitably led to a conflict between the metaphysical preservation of dogma and the historical commitment of testimony. In this way the concrete existence of Jesus of Nazareth, the anointed one of God, is the essence of Christianity that is universalized not by abstraction but by the communication of the life of grace in the Spirit.